A LARGE HUMAN CENTRIFUGE FOR EXPLORATION AND EXPLOITATION RESEARCH - Jack J.W.A. van Loon (Annales Kinesiologiae, 2015)
This paper addresses concepts regarding the development of an Altered Gravity Platform (AGP) that will serve as a research platform for human space exploration. Space flight causes a multitude of physiological problems, many of which are due to gravity level transitions. Going from Earth's gravity to microgravity generates fluid shifts, space motion sickness, cardiovascular deconditioning among other changes, and returning to a gravity environment again puts the astronauts under similar stressors. A prolonged stay in microgravity provokes additional deleterious changes such as bone loss, muscle atrophy and loss of coordination or specific psychological stresses. To prepare for future manned space exploration missions, a ground-based research test bed for validating countermeasures against the deleterious effects of g-level transitions is needed. The proposed AGP is a large rotating facility (diameter > 150 m), where gravity levels ranging from 1.1 to 1.5g are generated, covering short episodes or during prolonged stays of weeks or even months. On this platform, facilities are built where a crew of 6 to 8 humans can live autonomously. Adaptation from 1 g to higher g levels can be studied extensively and monitored continuously. Similarly, re-adaptation back to 1 g, after a prolonged period of altered g can also be investigated. Study of the physiological and psychological adaptation to changing g-levels will provide instrumental and predictive knowledge to better define the ultimate countermeasures that are needed for future successful manned space exploration missions to the Moon, Mars and elsewhere. The AGP initiative will allow scientific top experts in Europe and worldwide to investigate the necessary scientific, operational, and engineering inputs required for such space missions. Because so many different physiological systems are involved in adaptation to gravity levels, a multidisciplinary approach is crucial. One of the final and crucial steps is to verify the AGP concept by a large scientific community through feedback from various scientific societies. This facility will also serve clinical research on Earth, because a multitude of health problems such as osteoporosis, frailty of the elderly, inactivity, sarcopenia, obesity, insulin resistance and diabetes, cardiovascular problems, connective tissue ageing and immune deficiency, among others stand to benefit from the fundamental insights into the effects of our ever-present terrestrial gravity gained with such a novel research platform.